ASSOCIATIVE FACTORS OF OBESITY AMONG ADOLESCENTS IN SELECTED SCHOOLS OF PIMPRI CHINCHWAD MUNICIPAL CORPORATION OF PUNE CITY, MAHARASHTRA - M, Salvirupali; A, Chandekarpratibha (International Journal of Clinical and Biomedical Research, 2015)
Context: WHO has declared obesity as one of the most neglected disease of significant public health importance of this century. WHO official website dedicated to controlling the global obesity epidemic states. At the other end of malnutrition scale, obesity is one of today’s most obviously visible, yet most neglected public health problem. This study was conducted to assess associative factors of obesity among adolescents and its correlation with selected demographic variables. Methods and Material: A prospective cross sectional, descriptive study, conducted on 100 adolescents studying in affluent schools of PCMC were examined. Cross sectional research design, Probability sampling technique was used. Adolescents aged 13-16 years of age studying in affluent English medium schools located in Pimpri Chinchwad area were selected. Results & Discussion: The data showed that prevalence of obesity among adolescents was more while underweight was less as evidenced by BMI. Study results showed that prevalence of obesity increased as the increased BMI. More consistent waist height ratio was observed than waist hip ratio and it was also found 39% adolescents had central obesity. 24% of males and 8% of girls consumed less total calories per day than required while 50% of males and 10% of females consumed more than required total calories per day. Conclusion: Study revealed that High BMI, presence of abdominal fat and dietary pattern are important associative factors of obesity among adolescents. KEYWORDS: Associative Factors; Obesity; Adolescents; Selected Schools.